LATIHAN SENAM TERHADAP KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS DI DESA PALUH BAJI KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG - Samuel Ginting; Chaidir Saputra Harahap; Grace Erlyn Damayanti; Pitri Ani; Syatria Wati; Juni Mariati Simarmata (JURNAL PENGMAS KESTRA (JPK), 2021)
Diabetes mellitus was more commonly known as diabetes was a disease or disorder that affects the ability of the body in amounts or concentrations of glucose or sugar in the blood than normal. Accorded to WHO (2009), the number of patients with Diabetes Mellitus as many as 7.0 million people, WHO estimates the number of patients with diabetes mellitus have increased in the year 2030 as many as 12.0 million people. This type of research was a quasi-experiment (quasi experiment) with a model of design time series design. This study aims to determine the effect of exercise on blood sugar levels in people with diabetes mellitus in the Desa Paluh Baji Kecamatan Pantai Labu Kabupaten Deli Serdang 2012. The population in this study were all patients with diabetes mellitus in the Desa Paluh Baji Kecamatan Pantai Labu Kabupaten Deli Serdang week as many as 54 people, with a sample of as many as 35 people. Sampled technique with a non probability purposive sampling technique approach. From the results obtained that all respondents have a blood sugar> 120 mg / dl before exercise and the majority of respondents had a blood glucose <120 mg / dl as many as 28 people (20.0%) performed after exercise. Based on the results of statistical tests obtained p-value = 0.012 (Î± = 0.05) we can conclude there was significant influence between blood sugar levels before and after exercise. It was recommended to patients with diabetes mellitus in order to apply the exercises in an effort to decrease blood sugar levels and to further research in order to further develop the material handling problems researchers about how blood sugar levels in people with diabetes mellitus.